Women’s attitudes and beliefs towards specific contraceptive methods in Bangladesh and Kenya - Machiyama, Kazuyo; Huda, Fauzia Akhter; Ahmmed, Faisal; Odwe, George; Obare, Francis; Mumah, Joyce N.; Wamukoya, Marylene; Casterline, John B.; Cleland, John (Reproductive health, 2018)
Background Missing from the huge literature on women’s attitudes and beliefs concerning specific contraceptive methods is any detailed quantitative documentation for all major methods in low- and middle-income countries. The objectives are to provide such a documentation for women living in Matlab (rural Bangladesh), Nairobi slums and Homa Bay (rural Kenya) and to compare the opinions and beliefs of current, past and never users towards the three most commonly used methods (oral contraceptives, injectables and implants). Methods In each site, 2424 to 2812 married women aged 15–39 years were interviewed on reproduction, fertility preferences, contraceptive knowledge and use, attitudes and beliefs towards family planning in general and specific methods. We analysed the data from round one of the prospective cohort study. Results While current users typically expressed satisfaction and held more positive beliefs about their method than past or never users, nevertheless appreciable minorities of current users thought the method might pose serious damage to health, might impair fertility and was unsafe for prolonged use without taking a break. Larger proportions, typically between 25% and 50%, associated their method with unpleasant side effects. Past users of pills and injectables outnumbered current users and their beliefs were similar to those of never users. In all three sites, about half of past injectable users reported satisfaction with the method and the satisfaction of past implant users was lower. Conclusions High levels of contraceptive use can clearly co-exist with widespread misgivings about methods, even those that are widely used. Serious concerns about damage to health, long term fertility impairment, and dangers of prolonged use without taking a break were particularly common in the Kenyan sites and these beliefs may explain the high levels of discontinuation observed in Kenya and elsewhere in Africa. This documentation of beliefs provides useful guidance for counselling and informational campaigns. The generally negative views of past users imply that programmes may need not only to improve individual counselling but also strengthen community information campaign to change the overall climate of opinion which may have been influenced by dissatisfaction among past users.